Cutibacterium avidum: A rare but expected agent of breast implant infection (2019)
ABSTRACT: Cutibacterium avidum is largely commensal and part of the skin microbiota, recently recognized as a pathogen that causes surgical site infections, especially in the presence of implants or medical devices. We present a 50-year-old woman with Cutibacterium avidum infection associated with breast implant augmentation, which required the removal of the implants to achieve the cure. As a skin commensal, Cutibacterium avidum previously was considered of low pathogenicity, but is now recognized as a causative organism of serious spontaneous and surgical site infections. It should not be routinely disregarded without further investigation, particularly if clinical signs of infection are present.